Identifying non-stationary groundwater level response to North Atlantic ocean- atmosphere teleconnection patterns using wavelet coherence - Holman, Ian P.; Rivas Casado, Monica; Bloomfield, John P.; Gurdak, Jason J. (Springer Science Business Media, 2011)
The ﬁrst comprehensive use of wavelet methods to identify non-stationary time- frequency relations between North Atlantic ocean-atmosphere teleconnection patterns and groundwater levels is described. Long-term hydrogeological time series from three boreholes within different aquifers across the UK are analysed to identify statistically signiﬁcant wavelet coherence between the North Atlantic Oscillation, East Atlantic pattern, and the Scandinavia pattern and monthly groundwater-level time series. Wavelet coherence measures the cross- correlation of two time series as a function of frequency, and can be interpreted as a correlation coefﬁcient value. Results not only indicate that there are common statistically signiﬁcant periods of multiannual-to-decadal wavelet coherence between the three teleconnection indices and groundwater levels in each of the boreholes, but they also show that there are periods when groundwater levels at individual boreholes show distinctly different patterns of signiﬁcant wavelet coherence with respect to the teleconnection indices. The analyses presented demonstrate the value of wave- let methods in identifying the synchronization of groundwater-level dynamics by non-stationary climate variability on time scales that range from interannual to decadal